Insurrection and Integration: The Indian “Mutiny” of 1857 and the Theatrical Renegotiation of Ethnic Alterities - Marty Gould (Cahiers Victoriens et Edouardiens)
For contemporary British observers, the Indian Mutiny of 1857 was not so much about India as it was about Britain. The following essay examines the culturally introspective nature of the “Mutiny plays” and their persistent exploration of British nationalism. Theatrical representations of the mutiny have been given far less critical attention than the novels, historical accounts, and periodical articles that were inspired by the conflict. Yet the theatre was committed to visually recreating the conflict for a deeply concerned domestic British audience. In the face of this colonial rebellion, British playwrights produced images of metropolitan cultural consolidation, mobilizing Scottish characters to forge a broader, Celtically inflected British identity that ideologically aligned the people of England and Scotland in clear opposition to the mutinous hordes of India. Through a peculiar, though consistent, cultural compression, plays about the Mutiny deploy kilts and bagpipes as emblems of a culturally inclusive, heterogeneous Britishness while simultaneously reducing India’s distinct ethnic groups to a culturally undifferentiated, and inassimilable, mass. Set loose upon the theatrical stage, the sharp juxtaposition of these collapsed racial and cultural identifications helped to transform an imperial crisis into a metropolitan project of nationalist reconstruction.